International perspective on common core competencies for occupational physicians: a modified Delphi study. Issue 7 (13th April 2016) - Lalloo, Drushca; Demou, Evangelia; Kiran, Sibel; Cloeren, Marianne; Mendes, René; Macdonald, Ewan B
Abstract : Objectives: The competencies required of occupational physicians (OPs) have been the subject of peer-reviewed research in Europe and individual countries around the world. In the European Union (EU), there has been development of guidance on training and common competencies, but little research has extended beyond this. The aim of this study was to obtain consensus on and identify the common core competencies required of OPs around the world. Methods: A modified Delphi study was carried out among representative organisations and networks of OPs in a range of countries around the world. It was conducted in 2 rounds using a questionnaire based on the specialist training syllabus of a number of countries, expert panel reviews and conference discussions. Results: Responses were received from 51 countries around the world, with the majority from Europe (60%; 59%) and North and South America (24%; 32%) in rounds 1 and 2, respectively. General principles of assessment and management of occupational hazards to health and good clinical care were jointly considered most important in ranking when compared with the other topic areas. Assessment of disability and fitness for work, communication skills and legal and ethical issues completed the top five. In both rounds, research methods and teaching and educational supervision were considered least important. Conclusions: This study has established the current priorities among OPs across 51 countries of the common competencies required for occupational health (OH) practice. These findings can serve as a platform for the development of common core competencies/qualifications within specific geographical regions or internationally. This is particularly pertinent with globalisation of commerce and free movement within the EU.